2013
DOI: 10.1063/1.4820763
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pulse conditions effects on reliability in GaN-based high electron mobility transistors by transient temperature measurements

Abstract: The forward Schottky characteristic method, utilizing the temperature dependence of forward gatesource Schottky junction voltage, has been used to measure the transient temperature rise under DC and cycle pulse for multi-finger AlGaN/GaN high electron mobility transistor. The effect of electrical pulse on channel temperature has been studied. The transient temperature rise of channel under pulses with different duty cycles and frequencies are determined, respectively. The measurement results show that operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This method has been validated in the literature [7,8]. We have previously presented our selection of the physical models in detail [8,18]. Table 1 lists the parameters of the material used in the transient temperature simulations.…”
Section: Resultsmentioning
confidence: 99%
“…This method has been validated in the literature [7,8]. We have previously presented our selection of the physical models in detail [8,18]. Table 1 lists the parameters of the material used in the transient temperature simulations.…”
Section: Resultsmentioning
confidence: 99%
“…Due to its military value, the study of HPM effects has also become a hot spot in recent decades. Y. M. Zhang et al studied the thermal characteristics of the GaN HEMT device under the electrical pulse of different duty cycles and frequency and found that low duty cycle and high-frequency operation are beneficial in improving lifetime and performance reliability [20,21]. Y. Q. Liu et al found that HPM can cause the non-linear response of HEMT, and the research results show that the cause of this phenomenon is tunneling and impact ionization [8].…”
Section: Introductionmentioning
confidence: 99%